MODEL AKTIVASI PERAN BANK SYARIAH DALAM MANAJEMEN USAHA PENGEMBANGAN USAHA TERNAK SAPI POTONG - Suyoso Putra, Yuniarti Hidayah; Yati, Sri (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This study aimstounderstand thepotential picture of beef cattle businessinIndonesia, to identifythemainissues of the business, how to establish strong beef cattle business, anddevelop amodel ofIslamic banksactivation inthe beef cattle business. The study employed a qualitativedescriptivemethod. The secondarydata are used which derived from theMinistryof AgricultureandLivestockandrelatedservicesfrom 2009to 2012,BPS and BankIndonesiadatarelated to therole ofIslamic banksin agricultureandanimal husbandry, andthewebsiteof Islamicbanks.The results showed that Islamic banksare reluctant toget involvedin this businessdue to a highriskventure. Therefore, tooptimize theactiveroleof Islamic banks, a model will be establishedrelatedtothe roleof Islamic banksinthe cattle business. Islamic bankscan contribute directlyandindirectlyto solveproblemsandestablish the beefcattle business. Direct roleis performedbydesigning contractapproach infinancing, whereasindirectroleis throughCorporate SocialResponsibilityprogramtoimprovethe basicconditionsoffarmers andthe business, if the bank is not yetconvinced thatgiving thedirect financing,the businesswill besuccessful.